Evaluating a South African mobile application for healthcare professionals to improve diagnosis and notification of pesticide poisonings - Kabanda, Siti (Department of Public Health and Family Medicine, 2017)
Acute pesticide poisoning (APP) is a major global public health problem, particularly in low- and middle-income countries (LMICs) including South Africa. However, healthcare professionals (HCPs) worldwide have limited training in handling environmental health risks such as from pesticide exposures. Most HCPs lack basic training on APP and, this presents a challenge to HCPs when diagnosing and notifying pesticide-related poisonings. With a recent increase in mobile application technology, this gives a convenient platform to provide training support for HCPs in their clinical practice. An example is the integration of a South African pesticide notification guideline into an existing Emergency Medicine (EM) mobile application. This pesticide notification guideline (PNG) within the EM mobile application aims to provide an immediate point-of-care tool to help HCPs in diagnosis and notify pesticide poisoning cases. Despite this useful platform for training HCPs, there are limited studies that have evaluated mobile applications or technologies to promote HCPs training in LMICs. This study, therefore, aimed to evaluate the Centre for Environmental and Occupational Health Research (CEOHR)'s PGN adapted for the EM mobile application as a tool for improving HCP's ability to diagnose and report APPs. The protocol (Part A) provides information and a justification for the research study and, describes the methods used to gather and analyse the data. The extended literature review (Part B) provides an overview of studies assessing HCPs' knowledge of and training in pesticide poisonings and the role mobile health technologies play in improving HCPs' knowledge and training in clinical practice. Furthermore, the literature review illustrates the relevant theoretical frameworks and concepts that helps to understand HCPs' behaviour changes when using clinical guidelines or algorithms. The journal manuscript article (Part C) provides this study's research findings and how it could contribute to the body of knowledge. A total of 50 emergency medicine physicians and registrars participated in the